Monetary financing in the euro area: A free lunch? - Silke Tober (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2015)
Two recent proposals for overcoming the euro area crisis make the case for monetary financing of the public sector. Watt (2015) proposes that the ECB finances public investment directly, Pâris and Wyplosz (2014) contend that public debt may be effectively restructured by burying parts of it in the balance sheet of the Eurosystem. Both proposals place the ECB at the center of matters generally considered to be fiscal in order to circumvent existing fiscal and political constraints. This paper argues that neither monetary debt retirement nor monetary financing of EU investment are a free lunch. Both proposals fudge the line between monetary and fiscal policy thereby ignoring valid reasons for separating these two macroeconomic policy areas. All monetary policy measures impact on government finances; whether monetary policy actions cross the fiscal policy line, however, depends primarily on the underlying motivation of the action. In the case of the two proposals the motivation is unambiguously fiscal. – – Zwei neuere Vorschläge zur Überwindung der Krise im Euroraum plädieren für eine monetäre Finanzierung des öffentlichen Sektors. Watt (2015) schlägt vor, dass die EZB öffentliche Investitionen direkt finanziert, während Pâris and Wyplosz (2014) argumentieren, dass die öffentliche Verschuldung durch eine teilweise Umschichtung in die Bilanz des Eurosystems erfolgreich umstrukturiert werden könne. In beiden Vorschlägen übernimmt die EZB Aufgaben, die gemeinhin dem finanzpolitischen Bereich zugeordnet werden. In diesem Papier wird argumentiert, dass weder eine Umschichtung der Verschuldung zur Zentralbank noch eine monetäre Finanzierung öffentlicher Investitionen ein "free lunch" sind. Beide Vorschläge vermischen zudem die Grenze zwischen Geld- und Finanzpolitik und ignorieren damit wichtige Gründe für die Trennung beider Politikbereiche. Geldpolitische Maßnahmen beeinflussen die öffentlichen Haushalte zwar zwangsläufig; ob eine geldpolitische Maßnahme aber die Grenze zur Finanzpolitik überschreitet, hängt primär von der zugrundeliegenden Motivation ab. Im Falle beider Vorschläge ist die Motivation eindeutig finanzpolitisch.
Keywords: 330